Diploid genome assembly of the Malbec grapevine cultivar enables haplotype-aware analysis of transcriptomic differences underlying clonal phenotypic variation - Calderón, Pablo Luciano Sebastian (2024)
To preserve their varietal attributes established grapevine cultivars (Vitis vinifera L. ssp. vinifera) must be clonally propagated, due to their highly heterozygous genomes. Malbec is a France-originated cultivar appreciated for producing high-quality wines, and is the offspring of cultivars Prunelard and Magdeleine Noire des Charentes. Here, we have built a diploid genome assembly of Malbec, after trio binning of PacBio long reads into the two haploid complements inherited from either parent. After haplotype-aware deduplication and corrections, complete assemblies for the two haplophases were obtained with very low haplotype switch-error rate (<0.025). The haplophases alignment identified >25% of polymorphic regions. Gene annotation including RNA-seq transcriptome assembly and ab initio prediction evidence resulted in similar gene model numbers for both haplophases. The annotated diploid assembly was exploited in the transcriptomic comparison of four clonal accessions of Malbec that exhibited variation in berry composition traits. Analysis of the ripening pericarp transcriptome using either haplophases as reference yielded similar results, although some differences were observed. Particularly, among the differentially expressed genes identified only with the Magdeleine-inherited haplotype as reference, we observed an over-representation of hypothetically hemizygous genes. The higher berry anthocyanin content of clonal accession 595 was associated with increased abscisic acid responses, possibly leading to the observed overexpression of phenylpropanoid metabolism genes and deregulation of genes associated to abiotic stress response. Overall, the results highlight the importance of producing diploid assemblies to fully represent the genomic diversity of highly heterozygous woody crop cultivars and to unveil the molecular bases of clonal phenotypic variation.